Correlations between Reading Disabilities and Learning Disabilities - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to reveal correlations between reading disabilities and learning disabilities. These problems need to be explained and teachers need to have reasonable solutions. Number of school-children with learning disabilities is increasing and teacher is not able to find the best and most precise ways of diagnostics and treatment/intervention. Causes of learning disabilities are different: brain damage or distorted functioning of it; auditory or visual perception and operating problems; language acquisition or processing problems etc. Symptoms are mostly noticed in the main areas – reading, writing and mathematics. Reading disabilities are one of the most obvious and serious problems which are to be noticed and taken into account in teacher’s actions. It is necessary to diminish dropouts and to promote success of school-children. Main ideas of dyslexia are mentioned the same as findings in learning disabilities. Early warning signs of learning disabilities are mentioned and some suggestions for intervention are stated in this article.